(untitled) (Medical Forum Monthly, 2024)
Objective: The objective of this double-blind, comparative study evaluating efficacy and biochemical effects of optimized felodipine 10mg (F-7) as monotherapy with comparison to placebo in adult patient with essential hypertension. Study Design. Double-blind, comparative study Place and Duration of Study: This study was conducted at the Department of Biochemistry, University of Karachi from March 2011 to October 2011. Materials and Methods: This was multicenter randomized, double-blind, comparative study. Patients were randomized to receive once Felodipine (F-7) daily for 8 weeks and at the end of study efficacy and biochemical evaluation was done Results: The patients treated with optimized Felodipine 10mg (F-7) alone, blood pressure reduction was lower, although significant; reaching values of 140.2 ± 11.3 /87.9 ± 5.5 mmHg (p < 0.05 versus Placebo) by the end of eight weeks of treatment. . No significant variation of blood glucose was observed and different parameters of lipid profile were also observed during the eight weeks of treatment with antihypertensive regimen used. Thus, the drug regimens used may be considered neutral as regards glucose and plasma lipid metabolism profile because drug used at low doses. Conclusion: We can suggest that the high antihypertensive efficacy, good tolerability and no biochemical effects of the optimized Felodipine 10mg (F-7) it is an excellent option for the treatment of hypertension in a wide range of hypertensive patients, with a high potential to reduce cardiovascular risks.